2013
DOI: 10.4103/2230-8210.122644
|View full text |Cite
|
Sign up to set email alerts
|

A case of autoimmune hypoglycemia outside Japan: Rare, but in the era of expanding drug-list, important to suspect

Abstract: We are hereby reporting a case of a 72-year-old Indian man, who, in the absence of a detectable tumor, presented with symptomatic hypoglycemia in the postabsorptive state (3-5 h after meal). His serum levels of insulin and C-peptide were very high. He was not taking any hypoglycemic drug. Hypoglycemic episodes completely subsided after withdrawal of pentoprazole and incorporation of small frequent meals in the dietary plan. Six months after the initial presentation, the subject became free of hypoglycemic epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In a study that included 380 Japanese patients reported that approximately 50% had prior exposure to drugs such as methimazole, penicillamine, glutathione, hydralazine, procainamide and isoniazid. There are case reports of IAS in patients using sulfhydryl-containing proton pump inhibitors including pantoprazole and omeprazole (3, 8). The mechanism of development of IAS with sulfhydryl group-containing drug is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study that included 380 Japanese patients reported that approximately 50% had prior exposure to drugs such as methimazole, penicillamine, glutathione, hydralazine, procainamide and isoniazid. There are case reports of IAS in patients using sulfhydryl-containing proton pump inhibitors including pantoprazole and omeprazole (3, 8). The mechanism of development of IAS with sulfhydryl group-containing drug is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…She lost 6 pounds of weight, her HbA1c improved to 5.7% and anti-insulin antibody levels came down to 33 U/mL. Based on a report of pantoprazole-related IAS cases (3), her omeprazole was switched to an H2 receptor blocker famotidine. Over the next 12 months, she reported only two episodes of hypoglycemia.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common causes of hypoglycemia in non-diabetic patients are insulinoma, extra pancreatic tumors, and autoimmune hypoglycemia (1). The autoimmunity that causes hypoglycemia occurs in two ways: in-sulin receptor antibodies with insulin mimetic effects or insulin autoimmune syndrome characterized by insulin antibodies (1). The insulin autoimmune syndrome is characterized by spontaneous hypoglycemia, increased insulin levels, and increased circulating insulin antibodies, first described by Hirata et al in 1970 (2).…”
Section: Introductionmentioning
confidence: 99%
“…There are also publications showing association with other drugs, which most frequently include methimazole, along with others such as D-penicillamine, procainamide, isoniazid, hydralazine, glutathione, captopril, and imipenem (4). In addition, incidences related to alpha lipoic acid (5) and proton pump inhibitor (1,2) have also been reported.…”
Section: Introductionmentioning
confidence: 99%